Buddhist Doctrines and Acceptance of Change: A Psychological Empowerment Approach for Early Older Adults in the Aging Society - Traiwattanawong, Natchanan (Journal of Humanities and Social Sciences, Rajapruk University, 2026)
This study aims to analyze and synthesize an integrated conceptual framework that combines Buddhist doctrines, particularly the Three Characteristics of Existence and the Four Foundations of Mindfulness, with modern psychological concepts, namely Acceptance and Commitment Therapy and Mindfulness, in order to enhance psychological empowerment among early older adults in the context of the transition to a complete aging society. The study employed a documentary analysis approach, reviewing 30 relevant documents published between 2020 and 2025. The findings reveal that the Three Characteristics of Existence are conceptually consistent with key principles of Acceptance and Commitment Therapy. Specifically, anicca corresponds with the acceptance of life’s uncertainty, dukkha reflects the concept that experiential avoidance contributes to suffering, and anatta aligns with the notion of self-as-context. Meanwhile, the Four Foundations of Mindfulness correspond with mindfulness concepts in modern psychology. Kayanupassana relates to body observation techniques, vedananupassana corresponds with emotional awareness, cittanupassana aligns with awareness of cognitive processes, and dhammanupassana corresponds with values clarification. Based on this synthesis, the study proposes a three-dimensional integrated framework consisting of (1) Understanding, which focuses on developing insight into the nature of life’s changes (2) Practice, which emphasizes systematic training in the Four Foundations of Mindfulness and (3) Application, which involves applying knowledge and skills to manage real-life challenges. These three dimensions are interconnected and mutually reinforcing in a continuous process.